2015
DOI: 10.1007/s13197-015-1749-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the perforation level of recycled-LDPE bags on the modification of the atmosphere development, bioactive compounds content, and other qualities of Jalapeño peppers during storage

Abstract: The impact of modified atmosphere packaging on the content of selected bioactive compounds and other quality attributes of Jalapeño peppers has not been well studied. In this study, Jalapeño peppers were packed in low-cost bags (composed of recycled-LDPE) that had been perforated at several levels (0-4 holes). Packages were stored at 7 °C for 6 weeks. Samples of unpacked peppers were stored at 23 and 7 °C and were used as control groups. The quality of the peppers and the gas composition inside of the packages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In case of perforated packages, hydrocooled samples with packaging perforations of 2 (sample E), 4 (sample F) and 6 (sample G) were resistant to spoilage for 5.83 ± 0.41, 7.17 ± 0.41 and 5.67 ± 0.52 days, respectively, in room temperature and, 15.83 ± 0.41, 22.67 ± 0.52 and 21.17 ± 0.41 days, respectively, in refrigerated temperature after which, slight yellowing and rotting of the chillies were observed. The result agrees with the previous work done by de Jesús Ornelas-Paz et al [17] At 8 th day, nearly all chilli samples stored at room temperature were unmarketable in terms of colour and shape but at refrigerated temperature, storage life extended up to 20 days for sample F. Hence, during storage at either room or refrigerated temperature, it was observed that sample F was the most effective against spoilage. Once the spoilage was observed, the samples were considered unacceptable.…”
Section: Physical Parameters Of Fresh Akabaresupporting
confidence: 92%
“…In case of perforated packages, hydrocooled samples with packaging perforations of 2 (sample E), 4 (sample F) and 6 (sample G) were resistant to spoilage for 5.83 ± 0.41, 7.17 ± 0.41 and 5.67 ± 0.52 days, respectively, in room temperature and, 15.83 ± 0.41, 22.67 ± 0.52 and 21.17 ± 0.41 days, respectively, in refrigerated temperature after which, slight yellowing and rotting of the chillies were observed. The result agrees with the previous work done by de Jesús Ornelas-Paz et al [17] At 8 th day, nearly all chilli samples stored at room temperature were unmarketable in terms of colour and shape but at refrigerated temperature, storage life extended up to 20 days for sample F. Hence, during storage at either room or refrigerated temperature, it was observed that sample F was the most effective against spoilage. Once the spoilage was observed, the samples were considered unacceptable.…”
Section: Physical Parameters Of Fresh Akabaresupporting
confidence: 92%
“…Puncture tests were carried out on all fruit by pressing the probe vertically against two opposite equatorial sides of the same fruit. Firmness was measured as the average of the values measured on these both sides and expressed in N (de Jesús Ornelas-Paz et al, 2015;Sahoo et al, 2014).…”
Section: Firmnessmentioning
confidence: 99%
“…Koide and Shi (2007) reported only minor changes in AA in green peppers packaged in several films and kept refrigerated at 10 °C for 7 days. Ornelas-Paz et al (2015) found a similar content of AA in unpackaged and packaged, cold-stored jalapeño peppers; AA maintained quite constant during storage in both types of fruit. However, AA increased continuously in unpackaged peppers stored at 23 °C which was associated with postharvest ripening and dehydration.…”
Section: First Assaymentioning
confidence: 62%
“…In our work and, according to what was stated above, the decrease in the amount of β-carotene at the end of storage was attributed to the senescence of peppers. In a study carried out by Ornelas-Paz et al (2015), the amount of β-carotene was not altered during storage in unpackaged and packaged peppers that had been kept under refrigeration. ) found a continuous increase of total carotenoids in green chili peppers at the same time that the degradation of chlorophyll was taking place; they also found that both processes were slowed down due to a slower respiration rate when MAP was used.…”
Section: First Assaymentioning
confidence: 97%
See 1 more Smart Citation